ANALYZING NETIZEN RESPONSES TO CNN BREAKING NEWS ON TWITTER: EXPLORING GRICE'S COOPERATION VIOLATIONS AND IMPLICATIONS FOR DIGITAL MEDIA LITERACY EDUCATION IN NOVEMBER 2023 - Mujazin, M; Aghitsna, Laasya Ary (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2024)
This study analyzes violationsof maxim in CNN Breaking news twitter account. The study aims to achieve two objectives: (a) identify violations of Grice's cooperative principles in netizen responses to CNN Breaking News on Twitter during the November period, and (b) explain the reasons behind these violations. The research employs a qualitative descriptive method, utilizing data from netizen responses to tweet uploads on CNN Breaking news twitter in November. Data collection involves documentation and note-taking. The analysis reveals a total of 101 violations of Grice's cooperative principles, categorized into four main types: 19 (18.8%) violations of the maxim of quantity, 13 (12.9%) violations of the maxim of quality, 48 (47.5%) violations of the maxim of relation, and 21 (20.8%) violations of the maxim of manner. The reasons behind netizens flout the maxims include expressing emotion, conveying sympathy, expressing personal opinions, sarcasm, condescension, and diverting the conversation or topic. The study found instances of Grice's Cooperative Principle violations, indicating challenges in maintaining effective and cooperative communication in online discourse. The findings highlight the necessity for improved online communication ethics, emphasizing clarity, relevance, and respect. This is crucial for fostering more meaningful and respectful communication on social media platforms.